2021
DOI: 10.3389/fnmol.2021.708004
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Depression: Implications of Sex-Related Differences in Epigenetic Regulation

Abstract: Major depressive disorder (MDD) is a leading cause of disability worldwide. Although the etiology and pathophysiology of MDD remain poorly understood, aberrant neuroplasticity mediated by the epigenetic dysregulation of gene expression within the brain, which may occur due to genetic and environmental factors, may increase the risk of this disorder. Evidence has also been reported for sex-related differences in the pathophysiology of MDD, with female patients showing a greater severity of symptoms, higher degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 250 publications
(298 reference statements)
0
6
0
Order By: Relevance
“…Animal and human studies have shown that epigenetic mechanisms can regulate DNA transcription in response to environmental factors and may play a role in the pathological and physiological processes of depression [ 13 ]. Epigenetics refers to changes in expression level of a gene not involving changes in the DNA sequence, such as DNA methylation, histone modification, noncoding RNA, and chromatin remodeling [ 14 ]. DNA methylation means modification of the cytosine rings in a CpG dinucleotide using covalent binding of a methyl group of carbon 5 of cytosine of CpG dinucleotide in the genome by DNA methyltransferase.…”
Section: Introductionmentioning
confidence: 99%
“…Animal and human studies have shown that epigenetic mechanisms can regulate DNA transcription in response to environmental factors and may play a role in the pathological and physiological processes of depression [ 13 ]. Epigenetics refers to changes in expression level of a gene not involving changes in the DNA sequence, such as DNA methylation, histone modification, noncoding RNA, and chromatin remodeling [ 14 ]. DNA methylation means modification of the cytosine rings in a CpG dinucleotide using covalent binding of a methyl group of carbon 5 of cytosine of CpG dinucleotide in the genome by DNA methyltransferase.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis targeting the gender difference demonstrated that the differential lncRNA expression was more significant in female patients than that in males. A research reported that the expression of LINC00473 was downregulated in depressed patients [ 9 ]. More interestingly, another study revealed that LINC00473 was decreased in depressed females only [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used only male mice; therefore, our results are not necessarily generalizable to female mice. Given that previous evidence suggests sex-specific transcriptome changes in MDD and differences in antidepressant responsiveness between genders ( 62 , 63 , 64 ), further studies are necessary. Nonetheless, our study provides important information for subsequent studies aimed at exploring both male and female antidepressant responders.…”
Section: Discussionmentioning
confidence: 99%